2012
DOI: 10.1128/mcb.06440-11
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activity of Neural Retina Leucine Zipper (Nrl) Is Regulated by c-Jun N-Terminal Kinase and Tip60 during Retina Development

Abstract: Neural retina leucine zipper (Nrl), a key basic motif leucine zipper (bZIP) transcription factor, modulates rod photoreceptor differentiation by activating rod-specific target genes. In searching for factors that might couple with Nrl to modulate its transcriptional activity through posttranslational modification, we observed the novel interactions of Nrl with c-Jun N-terminal kinase 1 (JNK1) and HIV Tat-interacting protein 60 (Tip60). JNK1 directly interacted with and phosphorylated Nrl at serine 50, which en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 66 publications
1
14
1
Order By: Relevance
“…Previously, we reported that TIP60 was present at the promoter region of target genes such as IL6, IL8, Rho, and Ppp2r5c before key transcription factors, NF-κB (RelA/p65 subunit) and NRL, were recruited. 5,8) We proposed that TIP60 acts as a "histone code reader" that makes chromatin accessible to transcription factors. In this study, to test the hypothesis that TIP60 affected RelA/p65-dependent transcriptional activity through interaction with H3K4me3, we expressed FLAG-TIP60 in HepG2 cells and treated the cells with TNF-α.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that TIP60 was present at the promoter region of target genes such as IL6, IL8, Rho, and Ppp2r5c before key transcription factors, NF-κB (RelA/p65 subunit) and NRL, were recruited. 5,8) We proposed that TIP60 acts as a "histone code reader" that makes chromatin accessible to transcription factors. In this study, to test the hypothesis that TIP60 affected RelA/p65-dependent transcriptional activity through interaction with H3K4me3, we expressed FLAG-TIP60 in HepG2 cells and treated the cells with TNF-α.…”
Section: Resultsmentioning
confidence: 99%
“…TIP60 can function as a transcriptional coactivator or corepressor depending upon the cellular context and chromatin environment. As a coactivator, TIP60 interacts directly with numerous transcriptional activators, such as HIV-1 Tat, 1) type-I nuclear hormone receptors, 4) neural retina leucine zipper (NRL), 5) Pax6, 6) MyoD, 7) and NF-κB/p65. 8) In these instances, the coactivator function of TIP60 is mediated by its acetylation of histones at the promoter region.…”
mentioning
confidence: 99%
“…Previous reports showed that KAT5 is a critical co-activator in developmental pathways (Hattori et al , 39 ) and modulated the transcriptional activities of PAX6 and neural leucine zipper, which are key factors for retinal development. 24 , 25 , 38 In mouse embryonic development, KAT5 is also expressed at moderate levels in various organs including skeletal muscle. 40 In this regard, understanding of SOX4 acetylation by KAT5 will provide insight into how SOX4 is temporally regulated under differentiation conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 19 The presence of a MYST (MOZ, Ybf2/Sas3, SAS2, and TIP60) domain classifies KAT5 as a member of the MYST family of histone acetyltransferases (HATs), which participate in various cellular processes including transcriptional regulation, development, apoptosis, and DNA damage repair. 20 , 21 , 22 , 23 , 24 , 25 , 26 Through its HAT activity, KAT5 catalyzes the acetylation of core histones (H2A, H3, and H4) and several non-histone proteins including the p53 and MYC TFs. 27 , 28 , 29 , 30 , 31 , 32 In addition to a HAT domain, KAT5 has a chromodomain that enables interaction with methylated histones, and thereby it has potential as a histone code reader.…”
mentioning
confidence: 99%
“…The same can be said for the AP-1 partner, the Leu zipper transcription factor Nrl, which is required specifically for retinal development. The STPYSSVPPSPTFS motif surrounding Ser50 (underlined; the main JNK-mediated phosphorylation site in Nrl) is highly conserved among the Maf family transcription factors and required for efficient transcription of Nrl target genes; it is still unclear if this effect is mediated by TIP60 histone acetyltransferase or not, since JNK activity and TIP60 binding to Nrl-containing promoters did not correlate in vivo (347). Thus, these proposed partnerships require further evaluation.…”
Section: Jnk Phospho-switches Potentiating New Protein-protein Bindinmentioning
confidence: 99%